Dopant‐Free Crossconjugated Hole‐Transporting Polymers for Highly Efficient Perovskite Solar Cells. Issue 13 (28th May 2020) - Sun, Xianglang; Deng, Xiang; Li, Zhen; Xiong, Bijin; Zhong, Cheng; Zhu, Zonglong; Li, Zhong'an; Jen, Alex K.‐Y.
Abstract: Currently, there are only very few dopant‐free polymer hole‐transporting materials (HTMs) that can enable perovskite solar cells (PVSCs) to demonstrate a high power conversion efficiency (PCE) of greater than 20%. To address this need, a simple and efficient way is developed to synthesize novel crossconjugated polymers as high performance dopant‐free HTMs to endow PVSCs with a high PCE of 21.3%, which is among the highest values reported for single‐junction inverted PVSCs. More importantly, rational understanding of the reasons why two isomeric polymer HTMs (PPE1 and PPE2 ) with almost identical photophysical properties, hole‐transporting ability, and surface wettability deliver so distinctly different device performance under similar device fabrication conditions is manifested. PPE2 is found to improve the quality of perovskite films cast on top with larger grain sizes and more oriented crystallization. These results help unveil the new HTM design rules to influence the perovskite growth/crystallization for improving the performance of inverted PVSCs. Abstract : Two isomeric crossconjugated polymer hole‐transporting materials (HTMs) are developed to demonstrate significantly distinct device power conversion efficiencies (PCEs) under the same device fabrication conditions, 11.1% PPE1 and 19.3% for PPE2, which is found to be due to the improved quality of perovskite films made on top of PPE2 . More excitingly, the PPE2 ‐based perovskite solar cells (PVSCs) can further achieve a more impressive PCE of 21.3% through suitable surface passivation.